A review of the hyperiidean amphipod superfamily Archaeoscinoidea Vinogradov, Volkov & Semenova, 1982 (Crustacea: Amphipoda: Hyperiidea) - Zeidler, Wolfgang (Zootaxa, 2006)
A taxonomic review of the superfamily Archaeoscinoidea is presented, based predominantly on collections held by the Zoological Museum, University of Copenhagen, Denmark. The superfamily includes just one family, Archaeoscinidae, comprising two genera, Archaeoscina and Paralanceola. Prior to this review, Archaeoscina was known from two species, A. steenstrupi and A. stebbingi, with the status of the latter in doubt. Despite the loss of the unique type of A. stebbingi it is regarded as valid species for the time being. In addition, one new species of Archaeoscina, A. danae sp. nov., is described from the Pacific, Indo-Pacific and Atlantic Ocean. Paralanceola was known only from the unique type of P. anomala Barnard, 1930. Remains of the type were re-examined to determine unique characters such as the morphology of the second antennae. More specimens of P. anomala were not found but two additional species are described as new to science; P. wolffi sp. nov. from the South Pacific and Atlantic Ocean and P. oleseni sp. nov. from the tropical Atlantic Ocean. Two new characters were discovered during this study; the presence of a partial ventral suture between urosomites 2 & 3 in all specimens and the presence of male genital papillae in P. oleseni sp. nov. An examination of other members of the Physosomata revealed that these characters are also present in most other genera. Thus, they may be of phylogenetic significance. Keys are provided for genera and all species.